Lessons Learned From an Inter‐Institutional Graduate Course on Interdisciplinary Modeling for Water‐Related Issues and Changing Climate. (December 2013) - Saito, Laurel; Link, Timothy E.; Fernald, Alexander; Kohne, Lisa
Abstract Computer modeling is a useful tool for integrating approaches from different disciplines to address complex water and climate issues, but because academic training is typically disciplinary, many scientists and practitioners are not aware of modeling techniques in other disciplines or ways that different models can be integrated to address complex questions. Since 2005, we have conducted a course on interdisciplinary modeling that provides lectures and laboratory exercises from different disciplines as well as topics related to interdisciplinary modeling such as issues of scale and uncertainty. Students work in interdisciplinary teams to integrate modeling approaches from different disciplines to address issues related to water and climate. In this paper, we provide a description of course development and implementation, results of course evaluations of course content, lessons learned, and future needs for educating students about interdisciplinary approaches. We also provide results of surveys of course participants regarding course effectiveness and sustainability.